PROCESSING OF SQUID (Loligo sp.) CARTILAGE WASTE AS ANTIBACTERIAL HANDWASH - Fawzy, Nabiyl Ahmad; Awaluddin, Nurhikma; Muntasir, (MSJ : Majority Science Journal, 2024)
Squid cartilage (Loligo sp.) is known to contain chitosan compounds that have antibacterial activity. This study aims to formulate chitosan from squid cartilage (Loligo sp.) in the form of handwash preparations with concentrations of 0.1%, 0.2%, and 0.3% which are physically and chemically stable, and see the optimum concentration in inhibiting bacterial growth. The method used is laboratory experiments through three stages of extraction, namely deproteination, demineralization, and deacetylation as well as physical quality tests and ability tests before and after cycling tests which include organoleptic tests, homogeneity tests, pH tests, viscosity tests, foam height tests and antibacterial activity tests against Staphylococcus aureus and Escherichia coli bacteria by the method of sumuran. The results obtained based on the ANOVA test on Staphylococcus aureus bacteria are 0.000 and on Escherichia coli bacteria are 0.000. Chitosan from squid cartilage (Loligo sp.) can be formulated in the form of a handwash preparation and the most effective concentration in inhibiting Staphylococcus aureus and Escherichia coli is a concentration of 0.3%.